Diretividade em Português brasileiro: formas, funções e usos - Masetto Nicolai, Yan (Universidade Federal de São Carlos, 2023)
The present thesis focuses on analyzing, through the formal apparatus of Syntax, Semantics, and Pragmatics, the imperatives in Brazilian Portuguese and their characteristics, providing a description of the object regarding its structure - the syntactic hierarchy of functional nodes for φ-feature valuation, its semantic meaning, and the speaker-listener relationship, as well as the pragmatic interpretive path of directivity in Brazilian Portuguese. To achieve this, the present work unfolds into two sections: the first section deals with imperative sentences using Syntactic Cartography (CINQUE, 1999), and for the present purpose, there is a need to value the features of irrealis, futurity, and directivity in their respective nodes - MoodIrrealisP, AspectProximativeP, and MoodSpeechActP. Ultimately, we raise the issue of Brazilian Portuguese (BP) not belonging to the class of True Imperative (RIVERO; TERZI, 1995), proposing two higher structures: for cases like BP, the functional node is ForceP; for languages of the other type - such as Spanish - ImperativeP is employed. In the syntactic domain, we also discuss the presence of expressed subjects from an interlinguistic perspective, comparing with German and Spanish, as well as the limits of the indexical element being preferable in expressed uses. In the semantic part, we explore several approaches - Modal Theory (KAUFMANN, 2014), Performativity Theory (CONDORAVDI; LAUER, 2012), and Property Theory (PORTNER, 2004). The proposal adopted by the thesis is the Property theory, with adaptations - the speaker's wishes update the addressee's doings - through the typical engagement of imperatives. In this regard, the addressee's set of actions is updated, so that the interpretive process becomes Speaker Wishlist ≫ Addressee's To-Do-List (SWL ≫ AdTDL). In the pragmatic field, we argue in favor of a robust contextual selection, requiring the addressee to exist and be able to execute the action immediately after the utterance - or immediately following any stated temporal marker accompanying the imperative. The relevance of this Contextual Engagement Condition is that it does not apply to just any listener who hears an imperative but always to an intended audience. Furthermore, in this part, we analyze the phenomenon of the immediacy of directivity, which we refer to as the As-Soon-As-Possible interpretation, and as demonstrated in the end, it is a particularized implicature for each directive use, following all the principles and implicature rules. In Block II, the thesis focuses on forms other than imperatives to analyze and describe the phenomenon of directivity in utterances containing infinitives, gerunds, and participles, as well as the discussion of indirect requests through questions and the conditions in which Good/Bad Wishes are not directives. Thus, the thesis is divided to understand the phenomenon of directive force in Brazilian Portuguese with its various representations and forms, considering the configurations, rules, and limitations of each, as well as contextual issues. Finally, we bring together the blocks to conclude the characteristic features of directivity in the object language of the thesis, in order to draw parallels and indicate future scientific steps.
Directivity in brazilian Portuguese: forms, functions, and uses
Keywords: Português brasileiro; Imperativos; Diretividade; Interface teórico-formal; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA